VD_FINDINFO Réc-civile / 2012 / 13 vom 16. April 2012 - VD Tribunal cantonal (2012)
RÉCUSATION, MOYEN DE DROIT | 319 let. a CPC (CH), 321 al. 2 CPC (CH), 47 al. 1 let. f CPC (CH), 49 CPC (CH), 8a al. 3 CDPJ